First case of sunflower pattern calcific deposits and posterior capsular opacification on a pseudophakos. Issue 9 (12th September 2022) - Kaur, Kirandeep; Mishra, Snigdha; Gurnani, Bharat
Abstract: Calcification of the intraocular lens is an uncommon phenomenon that usually follows an uncomplicated surgery. Here, the authors report the first case of a 66‐year‐old male patient who presented with defective vision and was diagnosed with sunflower pattern calcific deposits and Elschnig pearl pattern posterior capsular opacification in the right eye. Abstract : Calcification of intraocular lens is uncommon and has been reported after cataract surgery, in scleral buckles, and implants. Coexistence with capsular opacification in a typical pattern in the same eye is an extremely rare phenomenon.